Road and trail running from 5 km to an ultra-marathon –trends in Switzerland from 1999 to 2019 - Thuany, Mabliny; Witthöft, Anja; Valero, David; Forte, Pedro; Weiss, Katja; Scheer, Volker; Nikolaidis, Pantelis Theo; Santos Andrade, Marilia; Cuk, Ivan; Knechtle, Beat (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. This study aimed to verify participation and performance in all road and trail-based races in Switzerland over twodecades (1999–2019).Methods. This is a secondary data-based study. We used 1,149,182 race records (788,818 from men and 360,364 fromwomen) from 407,944 unique finishers of the 5 km, 10 km, half-marathon, marathon, and ultra-marathon races in Switzerland,between 1999 and 2019. Data included the athletes’ genders, ages, race distances, and types of races (road or trail). The mento-women ratio was calculated and box plots were used to present differences according to gender, age groups, and racedistances in both terrains. Differences between the groups were calculated.Results. The men-to-women ratio has generally decreased in all race distances over the years. Runners competing in roadbased races were faster than those in a trail run in all distances. Men had faster finish times than women independent of age,except those competing in 10 km trail races. In road-based races, the men-to-women ratio was higher among older marathoners,while for trail runs, a higher men-to-women ratio was shown for older half-marathoners and participants in 10 km races.For 5 km, 10 km, half-marathon, and ultra-marathon races, a decrease in running speed differences was shown until theage of 50 years.Conclusions. In Switzerland, most of the runners competed in road-based races, but the interest in trail running hasincreased. The men-to-women ratio declined over time, which could show an increase in the interest of women to participatein endurance activities.
Keywords: exercise; endurance; age groups; mountain running; performance